2022
DOI: 10.3390/pathogens11090980
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Lactobacillus crispatus against Vaginal Colonization with Group B Streptococci in the Third Trimester of Pregnancy

Abstract: Background: A normal vaginal microbiota may protect the vaginal mucosa from colonization by potentially pathogenic bacteria, including group B streptococci (GBS). The aim of this study was to investigate the association between colonization with GBS and the presence of specific vaginal microbiota isolated from vaginal swabs in the third trimester of pregnancy. Methods: A semiquantitative culture of 1860 vaginal swabs from consecutive pregnant women in their third trimester was analyzed. The dominant bacteria, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…In this study, we found L. crispatus to be either absent or in very low concentration in women with BV, which is consistent with the known protective role of this species in normal vaginal microbiome (Verstraelen et al, 2009). L. crispatus has also been found to offer vaginal colonization resistance against Group B Streptococci during pregnancy (Starc et al, 2022). Although De Backer et al (2007) found L. crispatus to be present in varying concentrations across all Nugent grades, they used a cohort inclusive of pregnant Belgian women.…”
Section: Real-time Pcr Analysis Based On Gram Stain Categorysupporting
confidence: 83%
“…In this study, we found L. crispatus to be either absent or in very low concentration in women with BV, which is consistent with the known protective role of this species in normal vaginal microbiome (Verstraelen et al, 2009). L. crispatus has also been found to offer vaginal colonization resistance against Group B Streptococci during pregnancy (Starc et al, 2022). Although De Backer et al (2007) found L. crispatus to be present in varying concentrations across all Nugent grades, they used a cohort inclusive of pregnant Belgian women.…”
Section: Real-time Pcr Analysis Based On Gram Stain Categorysupporting
confidence: 83%
“…Prior studies have demonstrated inconsistent relationships between CV microbiota and GBS colonization in pregnancy. [7][8][9][10][11] One large study of pregnant individuals in Guatemala did not find any significant differences in the CV microbiota when comparing GBS RVþ and GBS RVÀ individuals; however, 16S rRNA sequencing was completed at >35 weeks' gestation, and the prevalence of GBS colonization in this population was less than half of that of our population. 9 Our findings are consistent with two other studies of pregnant individuals, both of which demonstrated an association between lower abundance of Lactobacilli among GBS colonized individuals.…”
Section: Results In the Setting Of What Is Knownmentioning
confidence: 99%
“…[3][4][5] While existing data have rigorously characterized the CV microbiota in both pregnant and nonpregnant individuals, 3,[6][7][8][9][10] only a few studies have begun to examine the relationship between the CV microbiota and GBS RV colonization in pregnancy. [7][8][9] A few studies have demonstrated an inverse association between Lactobacillus species and GBS colonization in the third trimester, 9,11 whereas others have not confirmed this. 7,8 Furthermore, recent works have demonstrated that antimicrobial peptide β-defensin-2 is associated with nonoptimal CV microbiota as well as bacterial vaginosis and sexually transmitted infections, but the impact of β-defensin-2 on GBS colonization in pregnancy has not yet been examined.…”
mentioning
confidence: 99%